M-Healthcare to facilitate self-management of chronic back pain - Hameed, Shihab Ahmed; Redha, N.; Sh. Ahmed, Mohammed; Sh. Ahmed, Ahmed (Journal of Scientific and Engineering Research, 2017)
In this era of IT and mobility, mobile application becomes an essential software application in software industry. Medical and healthcare applications are widely used in human life. With the increasing capabilities of mobile phones, software industry finds it as an important paradigm to develop mobile-health which increased tremendously. Chronic diseases become one of the famous diseases nowadays. It affects many people around the world. This makes people start to miss their comfortable life and may be their ability to perform their job properly. Patients with chronic diseases suffers from providing updated information to the medical doctors, high cost of visiting doctors and treatments, and some of the medical applications are complicated in term of usage. To overcome such weaknesses, this paper offers a suitable solution that can figure out and control the chronic disease. Mobile healthcare application offers updated information for doctors about patients, low cost, user friendly and can be used by different ages and cultures to help them to manage their chronic disease effect or pain. This paper will focus on back pain chronic disease where many people suffer. A prototype is developed to help people controlling their pain by recording or analyzing their pain and sharing their pain records with doctor or physiotherapist. The prototype is allowing chronic people to be energetic by providing them the exercises‟ video which can reduce their pain. This will help people to reduce their pains and allowing them to self-manage themselves in order to have a better life.